Validade de equações alternativas e da impedância bioelétrica para estimativa do estado nutricional em pacientes HIV/AIDS - Santos, Bruna dos (2020)
You know whether HIV, which causes AIDS, is characterized by attacking or the immune system. With an evolution that occurred after the introduction of combined antiretroviral therapy, important advances were observed, mainly with regard to the increased survival of those infected by the virus. However, the effects associated with therapy and prolonged use, caused problems related to a greater number of metabolic changes, one of which is the redistribution of body fat. Faced with this reality, body composition methods become an important tool to use information that helps in the diagnosis of the analyzed variables, especially with regard to the body fat of HIV-positive patients. Thus, the present study aims to analyze the accuracy of state indicators and body composition in patients with HIV / AIDS, both sexes, using a PH as the reference method. The data used in the investigated group were extracted from the database of the Cineanthropometry Laboratory (LABCINE) of the Physical Education and Sports Center (CEFD) of the Federal University of Santa Maria (UFSM), without qualifications 58 individuals with HIV/AIDS were selected, with 48 men and 10 women, between 15 and 66 years old. To determine body composition, the following evaluated methods were used: anthropometry (body mass, height, skinfolds and gauges), bioelectrical impedance and hydrostatic weighing, this being the reference method. Descriptive statistics was used for group characterization and the normality of the data was verified using the Kolmogorov-Smirnov test. A difference between the media was verified through the Student Standing Test for Variations IMC, IMC2,5, IMCgordura, CUN-BAE and IB and Wilcoxon Test Standing for Variations IAC and IMG. Pearson and Spearman's Correlation Coefficient was also used to determine the degree of association between the evaluation methods, as well as the Bland and Altman Test to verify the agreement of the results, and the Kappa Coefficient to determine the accuracy of the diagnoses a nutritional level of the target audience. For the analysis, the statistical program SPSS 20.0 was used, with a significance level of 5%. Finally, based on the results obtained, it was possible to conclude that: a) for the determination of %GC it can be seen that the tested methods tend to underestimate the result, with the smallest difference in the means found being -2.49% IB and the highest -4.15% for the IAC equation; b) considering the accuracy of the diagnosis for the nutritional status, it was noted that IMC2,5 showed significant agreement, but considered small, while IB and CUN-BAE showed a discreet and significant agreement with the diagnoses; c) for both equations, such as the IB, the results were not satisfactory for the cross-validation of these methods.